The phenomenon of creative images of Dimash Qudaibergen in the context of sustainable development of the cultural values of Kazakhstan - Zhanguzhinova, Meruyert (Creativity Studies, 2025)
The relevance of the research topic is justified by its contribution to the sustainable development of cultural values, using the example of the creative artistic activities of the renowned Kazakh singer, Dimash Qudaibergen. This scientific investigation identifies the insufficient coverage of the analysis of the singer’s stage image in the context of the importance of cultural values in shaping the concept of stage costumes. The aim of the research is to study the cultural connotations of stage costumes contributing to the sustainable development of the value orientations of Kazakh culture (through conceptual approaches in shaping values, artistic principles, functions of symbolic codes, signs, ornamentation, and archetypes). This study will address the exploration of cultural phenomena of Kazakhstan through the lens of national identity, contribution to the sustainable development of contemporary art, fostering creativity in art and culture, and influencing the younger generation through educational and media initiatives to promote cultural values. The research methodology encompasses theoretical methods, overview-conceptual analysis, inductive and deductive approaches, as well as the synthesis of data from these methodological approaches. The theoretical and practical significance of this research is demonstrated through the conceptual foundation for the creation of Qudaibergen’s visual stage costume image, interpreting his work as the “ontology of the music of the Eurasian Steppe”. The results of the research are conceptual justifications of the model of the ethnic costume of Kazakhstan, forming creative images of performers, and representing a phenomenon in the perspective of ensuring the sustainable development of Kazakhstan’s cultural values.